Preparation of a p-n heterojunction BiFeO3@TiO2 photocatalyst with a core–shell structure for visible-light photocatalytic degradation - Liu, Y.; Ding, S.; Xu, J.; Zhang, H.; Yang, S.; Duan, X.; Sun, Hongqi; Wang, S. (Kexue Chubanshe, 2017)
Magnetically separable bismuth ferrite (BiFeO 3 ) nanoparticles were fabricated by a citrate self-combustion method and coated with titanium dioxide (TiO 2 ) by hydrolysis of titanium butoxide (Ti(OBu) 4 ) to form BiFeO 3 @TiO 2 core–shell nanocomposites with different mass ratios of TiO 2 to BiFeO 3 . The photocatalytic performance of the catalysts was comprehensively investigated via photocatalytic oxidation of methyl violet (MV) under both ultraviolet and visible-light irradiation. The BiFeO 3 @TiO 2 samples exhibited better photocatalytic performance than either BiFeO 3 or TiO 2 alone, and a BiFeO 3 @TiO 2 sample with a mass ratio of 1:1 and TiO 2 shell thickness of 50–100 nm showed the highest photo-oxidation activity of the catalysts. The enhanced photocatalytic activity was ascribed to the formation of a p-n junction of BiFeO 3 and TiO 2 with high charge separation efficiency as well as strong light absorption ability. Photoelectrochemical Mott–Schottky (MS) measurements revealed that both the charge carrier transportation and donor density of BiFeO 3 were markedly enhanced after introduction of TiO 2 . The mechanism of MV degradation is mainly attributed to hydroxyl radicals and photogenerated electrons based on energy band theory and the formation of an internal electrostatic field. In addition, the unique core–shell structure of BiFeO 3 @TiO 2 also promotes charge transfer at the BiFeO 3 /TiO 2 interface by increasing the contact area between BiFeO 3 and TiO 2 . Finally, the photocatalytic activity of BiFeO 3 @TiO 2 was further confirmed by degradation of other industrial dyes under visible-light irradiation.